2019
DOI: 10.1039/c8an02337a
|View full text |Cite
|
Sign up to set email alerts
|

An implanted pH sensor read using radiography

Abstract: The constructed biosensor enhances the capability of traditional plain film radiography, enabling the noninvasive measurement of postoperative infection indicating chemical concentration such as pH on the implant surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Since the readings do not appear to systematically drift in time, noise is likely the main source of variation, and assuming the variation is noise sets an upper limit to the noise level. A precision of 80 μm is similar to the 100 μm interobserver variation we found in measuring displacement of radiopaque tungsten wires in a pH sensor based on pH-responsive hydrogels swelling[41]. It is somewhat worse than RSA analysis of tantalum beads (20-50 μm), but an order of magnitude better than direct fracture gap motion analysis with plain film X-rays.…”
Section: Discussionsupporting
confidence: 57%
“…Since the readings do not appear to systematically drift in time, noise is likely the main source of variation, and assuming the variation is noise sets an upper limit to the noise level. A precision of 80 μm is similar to the 100 μm interobserver variation we found in measuring displacement of radiopaque tungsten wires in a pH sensor based on pH-responsive hydrogels swelling[41]. It is somewhat worse than RSA analysis of tantalum beads (20-50 μm), but an order of magnitude better than direct fracture gap motion analysis with plain film X-rays.…”
Section: Discussionsupporting
confidence: 57%
“…We also previously showed that the same hydrogel swelling was minimally affected by physiological variation in buffer and tryptic soy broth bacterial culture ionic strength, temperature (25–40 °C), or long term incubation in a highly oxidative environment with hydrogen peroxide and copper ions. [ 41 ]…”
Section: Resultsmentioning
confidence: 99%
“…First, it was performed only in ex vivo bovine synovial fluid with added HCl and NaOH to adjust the pH (and previously in buffers and bacterial cultures with varying temperature, sodium chloride concentration, and oxidative environment). [ 41 ] The in vivo response may be different, especially after long term implantation.…”
Section: Resultsmentioning
confidence: 99%
“…Upcoming smart implants will likely integrate different measurement parameters beyond the here outlined devices assessing the mechanical competence of a fracture. Other groups for example investigate the use of electrochemical sensors to measure oxygen saturation [33] or target detection of implant associated infection by implantable pH sensors [34] . Callus formation sequence from weekly X-rays correlates with the curve drop.…”
Section: The Future -Closing the Loop With Active Implantsmentioning
confidence: 99%